Impact of resistance training on biokinetic abilities, functional variables, and the skill of free-throw shooting in female basketball players - Evan Ne'ma Kadhim; Naseer Mizher Abboud (Universidad de Murcia, 2023)
Article accepted. The article will be published here soon. Pending final quality checks.